Reflecting on the Creation of Virtual Laboratory Experiences for Biology Students - Myburgh, Pieter Hermanus (Frontiers in Education, 2022)
The COVID-19 pandemic challenged the status quo of higher education practices. With the transition to remote learning, students and faculty faced several challenges while making great strides in equalizing education access. Although theoretical aspects can be easily taught online, practical experiences are difficult to convey without dedicated laboratories and equipment. This is especially true in biological studies, where practical laboratory training significantly impacts the Student’s professional development. Presented here is an overview of some of the available resources that faculty can implement in their remote teaching curricula, a discussion on a possible approach toward creating in silico practicums, and potential challenges that could be experienced in creating such virtual laboratories (VL). To prevent another interruption in academic training, higher education institutions (HEIs) should focus on designing, developing, and implementing practical educational material. We propose that these resources be free and open-source, allowing for a global effort to create a standardized practical curriculum for basic biological technical skills.